THE DEVELOPMENT OF BIOLOGY PRACTICUM LEARNING BASED ON VEE DIAGRAM FOR REDUCING STUDENT COGNITIVE LOAD - Anna Fitri Hindriana (JETL (Journal of Education, Teaching and Learning), 2016)
Practicum is a process to gain meaningful knowledge through hands on and minds on activity, thusplan is needed in practicum  to connect the conceptual side and methodological side. Vee diagram-based Biology practicum learning was arranged to lower cognitive load of student in designing experiment so the practicum activity become meaningful because the students can see the interesting side in both conceptual side and methodological side. The design that being used in this study was educational study and development. Based on the result of this study, it can be informed that there is lowering of student cognitive load, both in extraneous load and germane load, in designing experiment based on vee diagram